Dalbavancin, Vancomycin and Daptomycin Alone and in Combination with Cefazolin against Resistant Phenotypes of Staphylococcus aureus in a Pharmacokinetic/Pharmacodynamic Model - Abdul-Mutakabbir, Jacinda C. (Antibiotics (Basel), 2020)
The most efficacious antimicrobial therapy to aid in the successful elimination of resistant S. aureus infections is unknown. In this study, we evaluated varying phenotypes of S. aureus against dalbavancin (DAL), vancomycin (VAN), and daptomycin (DAP) alone and in combination with cefazolin (CFZ). The objective of this study was to observe whether there was a therapeutic improvement in adding a beta-lactam to a glycopeptide, lipopeptide, or a lipoglycopeptide. We completed a series of in vitro tests including minimum inhibitory concentration testing (MIC) of the antimicrobials in combination, time-kill analysis (TKA), and a 168 h (7-day) one-compartment pharmacokinetic/pharmacodynamic (PK/PD) model on two daptomycin non-susceptible (DNS), vancomycin intermediate S. aureus strains (VISA), D712 and 6913. Results from our MIC testing demonstrated a minimum 2-fold and a maximum 32-fold reduction in MIC values for DAL, VAN, and DAP in combination with CFZ, in contrast to either agent used alone. The TKAs completed on four strains paralleled the enhanced activity demonstrated via the combination MICs. In the one-compartment PK/PD models, the combination of DAP plus CFZ or VAN plus CFZ resulted in a significant (p < 0.001) improvement in bactericidal activity and overall reduction in CFU/ml over the 7-day period. While the addition of CFZ to DAL improved time to bactericidal activity, DAL alone demonstrated equal and more sustained overall activity compared to all other treatments. The use of DAL alone, with or without CFZ and the combinations of VAN or DAP with CFZ appear to result in increased bactericidal activity against various recalcitrant S. aureus phenotypes.